Modification of thermoresponsive poly(N-isopropylacrylamide) by coupling with chitosan - Patingo, Rommel G. (Animo Repository, 2001)
Temperature-sensitive poly(N-isopropylacrylamide) (PiPAAm) exhibits a dramatic solubility change from soluble to insoluble, at its 'lower critical solution temperature' (LCST) in aqueous solution. When chemically cross-linked to form a gel, substantial discontinuous volume phase transition, from a swollen to collapsed state, in response to external temperature changes takes place at its 'lower critical gel transition temperature' (LCGTT). It is possible to alter the phase transition temperature behavior of PiPAAm polymers by coupling with chitosan. This is usually done to extend its utility in controlling drug delivery rates by temperature change, demonstrating its potential to achieve an intelligent drug delivery system. Chitosan is a non-toxic and biodegradable polysaccharide and has also been identified as a material for drug delivery systems.Modification of hydration-dehydration behavior or thermoresponsive PiPAAm is successfully achieved by coupling ester-activated endreactive PiPAAm with chitosan, via its amino groups, by the condensation reaction. Mono- and di-carboxy PiPAAm were prepared by free radical chain transfer to 3-mercaptopropionic acid (MPA) and 3,3-dithiopropionic acid, respectively, and converted to the more reactive ester by reacting with N-hydroxysuccinimide. Mono-coupled chitosan-PiPAAm gel exhibit an LCGTT of 36 degrees Centigrade while that of di-coupled chitosan-PiPAAm gel is 28 degrees Centigrade. The shift in the LCGTT of mono-coupled chitosan-PiPAAm could be attributed to high PiPAAm (LCST = 32 degrees Centigrade) chain mobility and the reduction of free amino groups of chitosan (LCGTT = 52 degrees Centigrade). Early dehydration of the di-coupled chitosan-PiPAAm gel is due to network formation in the gel which restricts chain movement.Water retention in mono-coupled chitosan-PiPAAm was also observed to be supported by free-moving PiPAAm chains but when low molecular weight chitosan was used, a dramatic decrease in the water retention ability of the gel was observed. The higher the degree of network formation in the di-coupled chitosan PiPAAm gel, the less is the water stored in the gel. The di-coupled PiPAAm-chitosan gel prepared using hydrolyzed chitosan, in contrast, was observed to be able to keep water efficiently.